Hierarchy and Characteristic of Storage Devices - Wibawa, I Nyoman Gautama Satria (International Research Journal of Management, IT & Social Sciences, 2015)
This paper explores information about hierarchy and characteristic of storage devices. Lack of knowledge about storage device that used by everyone in the world is the main background of this paper. People can understand what the different of types, function, advantage and disadvantage of several storage devices. This paper examines several articles from online source, and writerâs experience in use of storage devices. In order to gain a complete understanding of Storage Deviceâs types, divisions, functions and relationships, it is necessary to conduct a study that examines all parts of storage device. It is important to gain knowledge about storage device because in this modern age, every information stored as data more efficient, less space, and can easily accessible. The needs of each individual will be different, will be better if we know about what we do, what we need, and what best storage device that can suite our activities.